Pemberdayaan Ibu-Ibu PKK Rancabungur melalui Keterampilan dan Manajemen Keuangan Usaha Craft Decoupage - Nur Aini; Nur Asma (ITB Ahmad Dahlan Jakarta, 2020)
One of the efforts to increase family income is to increase creativity based on creative industries, such as making decoupage skills. This activity was held in Rancabungur Village, Rancabungur District, Bogor Regency. The PKM partners, namely the PKK RT 09 RW 05 women consisting of 25 participants. The purpose of this PKM activity is to teach the villagers with craft decoupage skills followed by business financial management. Our activity also aims to empower mothers to make decoupage from tissues to improve the family's economy and understand business financial management. The response of partners to this activity, all expressed interest. After obtaining the material skills and financial management of the craft decoupage business, the partners intend to practice it into one of the activities that generates family income, agreeing to 16 respondents (88.9%); disagree 0; neutral 2 respondents (11.1%). Partners interested in collaborating with business groups related to craft decoupage, both as material suppliers, craft decoupage craftsmen, or marketers of craft decoupage products, agree as much as 15 respondents (83.3%); disagree 0; neutral 3 respondents (16.7%). This activity will provide solutions to problems that develop in the community which can ultimately increase community income.